Colorectal cancer survivors' challenges to returning to work: A qualitative study. (22nd April 2019) - Gruß, Inga; Hanson, Ginger; Bradley, Cathy; McMullen, Carmit; Ritzwoller, Debra; Hodge, Stephanie; Varga, Alexandra; Banegas, Matthew P.
Abstract: Objective: To assess the challenges and needs of colorectal cancer (CRC) survivors in maintaining employment and returning to work (RTW) from the perspectives of both CRC survivors and employers in the United States. Methods: Semi‐structured interviews with CRC survivors ( n  = 10) and employers ( n  = 4) were transcribed, coded and thematically analysed using NVivo 12 software. Results: Workplace challenges for survivors included the following: inadequate availability of paid and unpaid leave, limited availability of workplace accommodations, and employers' lack of knowledge about CRC and the recovery process. Survivors were concerned about the lack of adequate financial resources to take unpaid leave and the need to relearn control of bodily functions. Workplace challenges for employers of cancer survivors included the following: limited institutional flexibility to provide individualised accommodations, communication with frontline managers about leave availability for employees and communication with employees about legal protections and limitations. Employers perceived that employees were unwilling to take leave. Conclusion: Colorectal cancer survivors in the US face difficult, sometimes insurmountable, challenges when trying to balance their physical and financial needs within the constraints of employment. Employers recognise challenges associated with this concern. Multi‐level interventions—ranging from flexible work schedules to training for frontline managers—might facilitate the RTW process.